Angiopreventive role of vitamins - Jośko, Jadwiga; Ratman, Rajmund; Ratman, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2008)
Recently much attention has been paid to the process of angiogenesis, which conditions and enables neoplasm growth and speeds up metastasis formation. Great hopes are connected with the possibility of the influence of vitamins on angiogenesis. That is why new ways of angiogenesis inhibition are being looked for. On the basis of in vivo and in vitro studies it was demonstrated that vitamins inhibit angiogenesis. The mechanism of angiogenesis inhibition by vitamins involves the transcription of genes of angiogenic factors such as VEGF, decreased expression of VEGF receptor, activation of transcription factors inhibition, angiopoietin 2 level decrease, increased apoptosis of endothelial cells, glutathione peroxidase inhibition, tyrosine kinase activity decrease, etc. Accordingly, it is possible that vitamins, whose role in this field is underestimated, could be a significant supporting component of neoplasm therapy.